Suppression of high-fat diet-induced obesity-associated liver mitochondrial dysfunction by docosahexaenoic acid and hydroxytyrosol co-administration. Issue 8 (August 2020) - Ortiz, Macarena; Soto-Alarcón, Sandra A.; Orellana, Paula; Espinosa, Alejandra; Campos, Cristian; López-Arana, Sandra; Rincón, Miguel A.; Illesca, Paola; Valenzuela, Rodrigo; Videla, Luis A.
Abstract: Objective: Obesity-induced by high-fat diet (HFD) is associated with liver steatosis, oxidative stress and mitochondrial dysfunction, which can be eluded by the co-administration of the lipid metabolism modulator docosahexaenoic acid (DHA) and the antioxidant hydroxytyrosol (HT). Methods: C57BL/6J mice fed a HFD were orally administered either with vehicle, DHA, HT or DHA+HT for 12 weeks. We measured parameters related to insulin resistance, serum lipid levels, liver fatty acid (FA) content and steatosis score, concomitantly with those associated with mitochondrial energy functions modulated by the transcriptional coactivator PGC-1a. Results: HFD induced insulin resistance, liver steatosis with n −3 FA depletion, and loss of mitochondrial respiratory functions with diminished NAD + /NADH ratio and ATP levels compared with CD, with the parallel decrease in the expression of the components of the PGC-1α cascade, namely, PPAR-α, FGF21 and AMPK, effects that were not observed in mice subjected to DHA and HT co-administration. Conclusions: Data presented indicate that the combination of DHA and HT prevents the development of liver steatosis and the associated mitochondrial dysfunction induced by HFD, thus strengthening the significance of this protocol as a therapeutic strategy avoiding disease evolution into more irreversible forms characterised by the absence of adequate pharmacological therapy in human obesity.